Between the Judicialization and the Attribution of Responsibilities. Frames in the News Coverage of Political Scandals in Chile (2014-2016) [Entre la Judicialización y la Atribución de Responsabilidades. Encuadres en la Cobertura Noticiosa de Escándalos Políticos en Chile (2014-2016)] - Jara-Reyes, R (El Profesional de la Informacion, 2020)
The mediatization of political scandals has become a common phenomenon in the most diverse political systems. However, we know little about how the media frame this information. To answer this question, we have developed a descriptive study on a series of recent political scandals denounced in the Chilean press. Taking as a temporary framework the news published between 2014 and 2016, we analyzed the total information (n=10011) published by a sample of eleven national media, on seven political scandals that occurred during the period. We have used the QDAMiner-Wordstat program to detect frame terms, from which we have been able to identify two large frames: one referring to the “Judiciali-zation of cases” and the other referred to the “Attribution of responsibilities”. The results are presented and discussed, examining some implications of the exercise for the understanding of the political scandals themselves and the way in which the Chilean periodic press presents and disseminates them. © 2020, El Profesional de la Informacion. All rights reserved.